CARACTERIZACIÓN DE PATRONES DE VARIACIÓN MORFOLÓGICA DE LA MYNTHOSTACHYS MEDIANTE MÉTODOS ESTADÍSTICOS MULTIVARIANTE - Gómez Ticerán, Doris (2007)
The main goal of the present study is to make the morphological characterization of the Mynthostachys 's (muña) collected in Cajatambo 's province, by means of statistical multivariant methods. The main method of Components discriminates against the existence of two Mynthostachys 's species(kinds) in Cajatambo 's community, those of abundant pubescencia (pubescentes) and those of scanty pubescencia (not pubescentes). The hypothesis test confirms that the vectors of averages based on the length of the petiole, length of the leaf, width of the leaf of the pubescentes and not pubescentes are different.